Effect of Drug Pressure on Promoting the Emergence of Antimalarial-Resistant Parasites among Pregnant Women in Ghana - Tornyigah, B.; Coppée, R.; Houze, P.; Kusi, K.A.; Adu, B.; Quakyi, I.; Coleman, N.; Mama, A.; Deloron, P.; Anang, A.K.; Clain, J.; Tahar, R.; et al. (Antimicrobial Agents and Chemotherapy, 2020)
The continuous spread of antimalarial drug resistance is a threat to current chemotherapy efficacy. Therefore, characterizing the genetic diversity of drug resistance markers is needed to follow treatment effectiveness and further update control strategies. Here, we genotyped Plasmodium falciparum resistance gene markers associated with sulfadoxine-pyrimethamine (SP) and artemisinin-based combination therapy (ACT) in isolates from pregnant women in Ghana. The prevalence of the septuple IRNI-A/FGKGS/T pfdhfr/pfdhps haplotypes, including the pfdhps A581G and A613S/T mutations, was high at delivery among post-SP treatment isolates (18.2%) compared to those of first antenatal care (before initiation of intermittent preventive treatment of malaria in pregnancy with sulfadoxine-pyrimethamine [IPTp-SP]; 6.1%; P = 0.03). Regarding the pfk13 marker gene, two nonsynonymous mutations (N458D and A481C) were detected at positions previously related to artemisinin resistance in isolates from Southeast Asia. These mutations were predicted in silico to alter the stability of the pfk13 propeller-encoding domain. Overall, these findings highlight the need for intensified monitoring and surveillance of additional mutations associated with increased SP resistance as well as emergence of resistance against artemisinin derivatives.
Research Article
Keywords: Plasmodium falciparum; artemisinin; drug resistance; pfdhfr; pfdhps; pfk13; sulfadoxine-pyrimethamine